Risk Management as a Specific Activity of Danube-Basin Enterprises - Chetverikova, Olena (Journal of Danubian Studies and Research, 2023)
The development of risk management at enterprises in Ukraine is a young and insufficiently studied phenomenon. The high importance of timely detection, assessment and risk reduction activities are being more and more important in the period of economic instability. The new conditions in which shipping companies operate make it necessary to investigate the implementation of risk management, to determine models of its application at certain stages of the enterprise's existence. Risk management issues are considered as an integral part of the company's management system. They are organically integrated, starting from the company's philosophy, its policies, and ending with business plans and day-to-day activities. Anticipated determination of types and characteristics of possible risks, timely control of risk situations at an enterprise contributes to clear definitions of systemic actions that have a positive impact on the financial and economic stability of enterprises, helps to specify the choice and substantiate rational decisions based on the adaptation of modern risk management models.